MARKETING STRATEGY FOR PRODUCTS IN SMALL AND MEDIUM ENTERPRISES (BANTAENG COFFEE CENTER) IN BANTAENG REGENCY - Ayu, Retno; Musfirah, A. (XXXX-XXXX, 2024)
The purpose of this study was to examine and analyse the constraints of product marketing strategies and development strategies of Small and Medium Enterprises (Bantaeng Coffee Center) in Bantaeng Regency. This research uses a qualitative approach with a descriptive type, aiming to analyse and understand in depth the condition of SMEs of Banyorang Coffee Processing Center in Bantaeng, through observation, interviews, and document analysis. The research will be conducted for two months in June and July 2024 at the SME, which is an important centre of coffee production. The focus of the research is the influence of the 7P Marketing Mix on SME business development, with research subjects including the Head of Marketing, Services Unit, Head of Production Unit, coffee farmers, and customers. The results showed that Bantaeng Coffee Centre SMEs face three main constraints in marketing strategy, namely coffee price fluctuations, processing constraints, and human resource quality, which significantly affect business competitiveness and sustainability. To overcome these challenges, the development strategies implemented include improving product quality, flexible pricing, promotion through various channels, human resource management, and optimisation of production processes, which overall contribute to improving SME competitiveness in local and international markets. Based on the results of the study, it can be concluded that Bantaeng Coffee Sentra SMEs face significant constraints in marketing strategies related to price fluctuations, processing, and quality of human resources, but have implemented effective development strategies through the 7P marketing mix to improve competitiveness and product quality in local and international markets.